THE CONTRIBUTION OF FISHERIES SUBSECTOR TOWARD GROSS REGIONAL DOMESTIC PRODUCT OF TANJUNGBALAI ASAHAN CITY NORTH SUMATRA PROVINCE - Matondang, Herbert; Yulinda, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on November 2017 in Tanjungbalai Asahan City North Sumatra Province. The location of the specified research by (purposive). The methods used in this research is survey method, data used in this research is the data set of the time of year 2011 until 2015. The aim of this study: 1) To analyze the fisheries subsector contribution toward Gross Regional Domestic Product (GDP) and employment in Tanjungbalai Asahan city in 2011-2015, 2) To analyze the base or non base fisheries subsector in the development of fisheries in Tanjungbalai Asahan based on Gross Regional Domestic Product and employment in the years 2011-2015.Based on the research, the contribution of the fisheries subsector Tanjungbalai Asahan toward Gross Regional Domestic Product in 2011-2015 are 17.10%, 16.63%, 16.23%, 16.18%, and 16.20%. While the contribution of the fisheries subsector in Tanjungbalai city based on indicators of labor from 2011-2015 are 23.50%, 22.82%, 21.35%, 20.60% and 19.80%. Fisheries subsector included base sector in Tanjungbalai Asahan during period 2011-2015 based on indicators of Gross Regional Domestic Product indicator with LQ value 7.53 - 7.86 and based on labor indicator LQ 9.05 - 10,57.Keywords : Contributions, GDP, Locationt Quetient (LQ)